2018
DOI: 10.1371/journal.pone.0196896
|View full text |Cite
|
Sign up to set email alerts
|

Why some women fail to give birth at health facilities: A comparative study between Ethiopia and Nigeria

Abstract: BackgroundObstetric complications and maternal deaths can be prevented through safe delivery process. Facility based delivery significantly reduces maternal mortality by increasing women’s access to skilled personnel attendance. However, in sub-Saharan Africa, most deliveries take place without skilled attendants and outside health facilities. Utilization of facility-based delivery is affected by socio-cultural norms and several other factors including cost, long distance, accessibility and availability of qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 40 publications
(48 reference statements)
7
65
0
1
Order By: Relevance
“…The reason of not feeling necessary to deliver in health facilities contributed the highest proportion among both marginalised (64%) and non-marginalised women (35%). This might be because of lack of awareness and understanding among women regarding the consequences of delivering their child at home without a skilled attendant and the benefits of institutional delivery, or it might be because of socio-demographic or cultural factors as illustrated by the study from Nigeria and Ethiopia which suggested lower likelihood of considering facility delivery as unnecessary among women with higher educational level [51]. It might be partly a reflection of their perception of the quality of services being delivered in health facilities as there is notable proportion of women who visited health facilities for ANC services but delivered babies at home.…”
Section: Discussionmentioning
confidence: 99%
“…The reason of not feeling necessary to deliver in health facilities contributed the highest proportion among both marginalised (64%) and non-marginalised women (35%). This might be because of lack of awareness and understanding among women regarding the consequences of delivering their child at home without a skilled attendant and the benefits of institutional delivery, or it might be because of socio-demographic or cultural factors as illustrated by the study from Nigeria and Ethiopia which suggested lower likelihood of considering facility delivery as unnecessary among women with higher educational level [51]. It might be partly a reflection of their perception of the quality of services being delivered in health facilities as there is notable proportion of women who visited health facilities for ANC services but delivered babies at home.…”
Section: Discussionmentioning
confidence: 99%
“…The racial/ethnic differences in maternal health service use and health outcomes have been a subject of growing interest in many countries [34][35][36][37]. The underlying factors behind this difference generally consist of lower socioeconomic status and perception of health and healthcare [29,38]. In some cultures, delivering at home may be considered normal or more culturally appropriate, thereby making the practice more common even when professional birthing services are available [38].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying factors behind this difference generally consist of lower socioeconomic status and perception of health and healthcare [29,38]. In some cultures, delivering at home may be considered normal or more culturally appropriate, thereby making the practice more common even when professional birthing services are available [38]. Sociocultural factors that shape healthcare-seeking behaviour are inherently more challenging to address and require special strategies such as replacing the existing norms and beliefs with the new ones through community education (role play) programs [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence revealed that several factors such as socio-economic status, maternal education, infrastructure, place of residence, women's experiences with healthcare providers and access to primary health care services significantly influence mothers' choice of place of delivery [13][14][15][16]. For example, a study from Nigeria and Ethiopia showed that women in the rural areas were more likely to regard facility delivery as unimportant and also complained about distance and inability to pay for the services [17].…”
Section: Introductionmentioning
confidence: 99%